A study of PM₂.₅ emitted from cooking activities in indoor environment - Leong, Meng Li (2015)
Cooking activities has the potential to cause adverse health effects and are strongly dependence on cooking parameters. The objective of this thesis is to quantify the emission from the cooking activities and identify the parameter that affect the particle generation the most in order to predict the associated health impacts towards chefs and kitchen workers. Counterbalanced measure design was employed to test the variables (i.e. cooking stove and temperature) and PM2.5 number concentration was measured in a controlled domestic kitchen with no mechanical ventilation by using a particle counter. The air change rate was measured using CO 2 tracer gas injection method using an IAQ meter. Based on a mass balance model, the emission rates of PM2.5 are calculated using the concentration decay rate derived from the measured concentration changing curve with time. The calculated rate is then used to quantify the particle decay rate, intake fraction and health impact. The difference and the relationship of stove and temperature are established by graph analysis and comparison. From the results obtained, the concentration emitted ranged from 0.31 >< 102 particles/cm3 to 1.53 x 104 particles/cm3. High PM2.5 concentration was observed during high temperature on electric stove. Type of stove used shows a relatively lower affects in particle emission than the cooking temperature use during experiment. The results show deviation from the existing studies due to the inconsistent performance of gas stove and the amount of chicken being cooked. This study significantly implied that high temperature cooking emitted the highest PM2.5 concentration and produce highest health impact. Recommendations were made according to hierarchy of control to correspond to the health impacts of the cooking emission.